2014
DOI: 10.1111/ijsw.12101
|View full text |Cite
|
Sign up to set email alerts
|

Promoting a higher retirement age: A prospect‐theoretical approach

Abstract: Demographic ageing and the necessity of raising the retirement age is one of the most frequently debated topics among European welfare policy experts. This study used prospect theory as developed in behavioural economics to explain public attitudes towards pension reforms. It argues that, in line with prospect theory, negative incentives are more useful in changing people's attitudes in favour of a higher statutory retirement age than are positive incentives. Therefore, in the case of increasing life expectanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…With decreasing fertility rates and increasing life expectancy, Germany is one of the fastest aging countries in the world, and predictions show that the share of people aged 65 and older will increase from 21 percent in 2010 to 28 percent in 2030 [1]. The welfare state's financial sustainability is under pressure due to a growing number of beneficiaries and less contributors, and in particular, the public pension system is expected to face severe economic problems [2][3][4][5][6]. In reaction, German policy makers have introduced several far-reaching reforms with the aim of increasing the retirement age and, thus, relieve the pension system of financial pressure: They lifted the statutory retirement age from 65 to 67 [7], introduced training programs for older workers [8], and abolished early retirement pathways [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…With decreasing fertility rates and increasing life expectancy, Germany is one of the fastest aging countries in the world, and predictions show that the share of people aged 65 and older will increase from 21 percent in 2010 to 28 percent in 2030 [1]. The welfare state's financial sustainability is under pressure due to a growing number of beneficiaries and less contributors, and in particular, the public pension system is expected to face severe economic problems [2][3][4][5][6]. In reaction, German policy makers have introduced several far-reaching reforms with the aim of increasing the retirement age and, thus, relieve the pension system of financial pressure: They lifted the statutory retirement age from 65 to 67 [7], introduced training programs for older workers [8], and abolished early retirement pathways [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of developed provinces (SDI 4 and SDI 5), NV, RE, and RL show significant and positive interaction effects. Although some studies indicate that increasing vehicle ownership will increase energy use and CO 2 emissions [83], improved social welfare and career prospects in developed regions still have a strong attraction to work with higher education [84,85]. The development of sustainable energy is mostly concentrated in technology-intensive industries.…”
Section: Results and Analysismentioning
confidence: 99%
“…Even rapid and ambitious increase in the retirement age (by 1 year each year to 65 years for both men and women) can only partly lessen the adverse impact of demographic trend. Domonkos (2015) in a study has concluded that in the case of increasing life expectancy, definedcontribution schemes that apply actuarial formulae linking the level of starting monthly pension benefits to life expectancy are more useful in promoting a higher retirement age than conventional defined-benefit schemes, which typically do not forge an automatic connection between longevity and starting pensions.…”
Section: Literature Reviewmentioning
confidence: 99%